Strategy for Improving the Competitiveness of Village-Owned Enterprises (BUMDes) (A Case Study in Bogor Regency) - Rachmat Ramadhan; Muhammad Findi; Nora Herdiana Pandjaitan (STIE Amkop Makassar, 2026)
Village-Owned Enterprises (BUMDes) play a strategic role in driving the rural economy, yet many face competitiveness challenges due to limited human resources, weak financial management, and low digital literacy. This study aims to: (1) identify the factors that strengthen the competitiveness of BUMDes in Bogor Regency; and (2) analyze the influence of product management and marketing, as well as formulate strategies to enhance community understanding in strengthening the competitiveness of BUMDes. A quantitative approach was employed, involving 30 respondents from both advanced and developing BUMDes. Data were analyzed using the IFE, EFE, IE, SWOT, and QSPM matrices. The results showed IFE and EFE scores of 3.02 and 3.00, respectively, placing the BUMDes in Cell I of the IE Matrix, which indicates a grow-and-build position. A total of 11 alternative strategies were formulated. The top-priority strategy was participation in government training programs to enhance financial management systems, digital technology skills, and human resource capacity (STAS = 5,61), followed by establishing independent business outlets (STAS = 5,48), and strengthening collaboration with BUMDes from other regions (STAS = 5,37). This study concludes that improving human resource capacity through government-facilitated training is the highest-priority strategy for addressing the internal weaknesses of BUMDes.